2020
DOI: 10.1016/j.scitotenv.2020.137929
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution and determining factors of different invasive ranks of alien species across China

Abstract: Determination of the geographical distribution and life-form spectra of alien species with different invasive abilities are essential to understand the process of invasion and to develop measures to manage alien species. Based on six classifications of Chinese alien species, environmental and social data, species density, life-form spectrum of alien species, and the relationship between species density of alien species and climatic or social factors were determined. The species density of alien species *Manusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…may also influence seed traits and germination progress, which needs further studies. But several studies have demonstrated that temperature and precipitation are the major factors affecting seed traits, plant performance, and distribution (Chamorro et al, 2018;Ramírez-Valiente et al, 2020;Zhou et al, 2020), as reported in the present study. Furthermore, the SEM analysis in this study indicated that the seed traits affected by MAT was stronger than MAP, which in line with previous study based on a worldwide meta-analysis (Moles et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…may also influence seed traits and germination progress, which needs further studies. But several studies have demonstrated that temperature and precipitation are the major factors affecting seed traits, plant performance, and distribution (Chamorro et al, 2018;Ramírez-Valiente et al, 2020;Zhou et al, 2020), as reported in the present study. Furthermore, the SEM analysis in this study indicated that the seed traits affected by MAT was stronger than MAP, which in line with previous study based on a worldwide meta-analysis (Moles et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…At present, the geographical distribution and density of alien species in China tend to decrease from the south and the east to the north and the west [40,41]. How will climate change affect China's future invasion of alien species?…”
Section: Biological Invasion Accelerates Expansionmentioning
confidence: 99%
“…Information on the current distribution of alien species in a geographical landscape is important to understand the ecological and environmental interactions shaping the introduction to naturalization continuum and has a broad range of applications regarding the management of naturalized and invasive species [47]. To estimate the geographical distribution of the species across the country, their occurrence records (latitude and longitude) species were extracted from GBIF (accessed on 5 July 2020; https://doi.org/10.15468/dl.7bkqza).…”
Section: Geographic Distributionmentioning
confidence: 99%